Weed management in direct-seeded rice under a long-term conservation agriculture-based rice (Oryza sativa)-wheat (Triticum aestivum) system - RAJ, RISHI; DAS, T K; PANKAJ; GHOSH, A; BHATTACHARYYA, RANJAN; CHAKRABORTY, DEBASHIS; PRASAD, SHIV; BANERJEE, TIRTHANKAR; KUMAR, VIKASH; SEN, SUMAN; GHOSH, SONAKA; ROY, ARKAPRAVA; et al. (The Indian Journal of Agricultural Sciences, 2022)
Weeds that occur in repeated flushes pose major challenges to direct-seeded rice (DSR). Zero till (ZT) DSR with crop residue influences weed interference considerably and can be substitutive to resource-intensive puddled transplanted rice (PTR). Field experiments were conducted at ICAR-Indian Agricultural Research Institute during 2018–19 involving conservation agriculture (CA)-based DSRs and weed control/herbicides treatments to appraise weed interference and productivity under an eight-year old CA-based rice-wheat system (RWS). All DSRs encountered more weeds than PTR. A double ZT system without residue [ ZTDSR-ZT wheat (ZTW); C1] had highest density and dry weight of grassy weeds, but a triple ZT system without residue [ ZTDSR-ZTW-ZT mungbean (ZTMB); C4] had highest density and dry weight of broad-leaved and sedge weeds. However, a triple ZT system with three crops residue [ ZTDSR + mungbean residue-ZTW + rice residue-ZTMB + wheat residue; C5)] could reduce weed interference significantly and led to 9.3% and 21.8% higher rice yield than C1 and C4, respectively. The application of pyrazosulfuron-ethyl 0.025 kg/ha pre-emergence followed by (fb) cyhalofop-butyl 0.100 kg/ha at 20 days after sowing (DAS), fb bispyribac-Na 0.025 kg/ha at 25 DAS (W4) led to significant reduction in grassy, broad-leaved and sedge weeds densities by 92.5, 96.6 and 67.7%, respectively. The triple ZT system with rice, wheat and mungbean residues (C5) combined with application of pyrazosulfuron-ethyl fb cyhalofop-butyl fb bispyribac-Na (W4) gave almost similar rice yield with PTR (C6). This may be recommended for adoption in Indo-Gangetic Plains (IGP) of India and in similar agro-ecologies of the tropics/sub-tropics.